Validation protocols for blood pressure-measuring devices: status quo and development needs. Issue 1 (February 2016) - Beime, Beate; Deutsch, Cornelia; Gomez, Timothy; Zwingers, Thomas; Mengden, Thomas; Bramlage, Peter
Abstract : Hypertension is a major risk factor for cardiovascular morbidity and mortality. Therefore, blood pressure self-measuring devices have emerged as valuable tools in patient care and the accuracy of these instruments is of fundamental importance. For this reason, several validation procedures for assessing the efficacy of blood pressure monitoring devices have been developed, including protocols by the Association for the Advancement of Medical Instrumentation, the British Hypertension Society, the German Hypertension League (Prüfsiegelprotokoll), and the International Protocol of the Working Group on Blood Pressure Monitoring of the European Society of Hypertension. In the past, most of the protocols have been reviewed and modified because of experiences gained during the validation studies carried out. However, each shows distinct differences, that is number and characteristics of patients required, blood pressure ranges, and the length of the validation procedure, which may result in unique advantages and/or limitations associated with their use. The continued standardization and evolution of these guidelines is essential to ensure the efficacy of blood pressure-measuring devices marketed for clinical and home use. Here, we aimed to compare four currently used validation protocols and to initiate a discussion on potential future improvements.